2010
DOI: 10.3758/mc.38.7.905
|View full text |Cite
|
Sign up to set email alerts
|

Implicit learning of fifth- and sixth-order sequential probabilities

Abstract: Serial reaction time (SRT) task studies have established that people can implicitly learn sequential contingencies as complex as fourth-order probabilities. The present study examined people's ability to learn fifth-order (Experiment 1) and sixth-order (Experiment 2) probabilities. Remarkably, people learned fifth-and sixth-order probabilities. This suggests that the implicit sequence learning mechanism can operate over a range of at least seven sequence elements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 38 publications
2
27
0
Order By: Relevance
“…A correlation would not be expected if the RT difference was a product of implicit processes. For this An effect of successor in the absence of a Successor 9 Session interaction occurs frequently in the traditional SRTT when there are six target locations and each target location has two possible successors (Remillard, 2008a(Remillard, , 2010Remillard & Clark, 2001). Thus, this pattern of results is not unusual.…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…A correlation would not be expected if the RT difference was a product of implicit processes. For this An effect of successor in the absence of a Successor 9 Session interaction occurs frequently in the traditional SRTT when there are six target locations and each target location has two possible successors (Remillard, 2008a(Remillard, , 2010Remillard & Clark, 2001). Thus, this pattern of results is not unusual.…”
Section: Resultsmentioning
confidence: 58%
“…Nonadjacent probabilities involve events that skip over at least one trial (e.g., lag 2-x and lag 4-x-2-x probabilities). More recently, Remillard (2010) has shown that people can learn fifth-and sixth-order probabilities. Thus, the mechanism for learning a sequence of responses in the traditional SRTT is remarkably powerful.…”
Section: Introductionmentioning
confidence: 98%
“…In the Perruchet task a long sequence of non-reinforced trials leads to an expectation that the next trial will be reinforced and vice-versa. Participants also respond to trial sequence information so that reaction time is reduced if the sequence is predictive of the response requirement and responses on trial n can be influenced by events on trial n − 5 or n − 6 (Remillard, 2010). Models for sequence learning include neural networks (Simple Recurrent Networks, SRNs) as well as in memory buffer frameworks similar to that used in the MECA model.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst the local learning environment assumption is common in studies of associative learning there are some examples of non-local influences in learning (e.g. the Perruchet Effect and sequence learning effects, McAndrew, Jones, McLaren, & McLaren, 2012;Perruchet, 1985;Remillard, 2010). Examples such as these suggest that unexplained learning curve variability might be understood as an effect of non-local influences.…”
Section: Non-local Influences On Associative Learning: New Data and Fmentioning
confidence: 99%
“…Finally, it is clear that young children (Saffran et al, 1996) and adults (Remillard, 2010) are sensitive to statistical regularities over a range of items. It also appears that being skilled at learning an artificial grammar in a sequential reaction time task is associated with strong reading skills (Misyak et al, 2010).…”
Section: Measuring Local Contextmentioning
confidence: 99%